PENGHASILAN VERSI AKUNTANSI, PAJAK DAN EKONOMI - BUDIARTHA, KETUT (Jurnal Ilmiah Akuntansi dan Bisnis, 2008)
Income is the key factor in valuing operational capability of a company. Failure in maintaining and using the income will cause failure of the company. Therefore, a thorough understanding about income would be necessary to avoid mistakes in income based-decision making. There is a difference in viewing income from the perspective of accounting and economic. In accounting view, income must have been realized, but economic version says that income also includes unrealized items. It is enough for accounting to view income based on conventional income statement, on the other hand, in order to reflect economic income, realized income statement must be adjusted to accommodate unrealized economic events. Accounting and tax view income without significant differences because the two consider the last destination of income would be the increase of capital/assets.
Keywords: economic income, Accounting income, tax view income